2020
DOI: 10.7759/cureus.9956
|View full text |Cite
|
Sign up to set email alerts
|

Acute Management of Iatrogenic Injury to Vertebral Artery With Central Venous Catheter in a Critically Ill Patient

Abstract: Vertebral artery (VA) injury during catheterization is quite rare given its anatomical position, but can be catastrophic when it is not discovered early on and managed accordingly. A multidisciplinary approach to the management of such injury has to weigh-in the benefits and risks of open surgery versus endovascular intervention. This can be done after thorough assessment of the patient’s condition and accessibility of the injured vessel. We report a case of a 90-year-old female admitted as a case of pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…They also identify 46 prior cases of vertebral artery catheterization during CVC placement, but only three cases of successful parent artery preservation with endovascular stent placement [8][9][10][11][12]. Most recently, Rayes et al presented a case in which they utilized an endovascular stent for vertebral artery preservation following iatrogenic injury [13]. Other endovascular treatments include embolization via either balloon or coil methods [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…They also identify 46 prior cases of vertebral artery catheterization during CVC placement, but only three cases of successful parent artery preservation with endovascular stent placement [8][9][10][11][12]. Most recently, Rayes et al presented a case in which they utilized an endovascular stent for vertebral artery preservation following iatrogenic injury [13]. Other endovascular treatments include embolization via either balloon or coil methods [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…However, certain limitations exist, that is, if the affected vertebral artery is the main blood supply, stenting should be considered, which leads to distal embolization risk. [ 2 ] Furthermore, based on the vertebral artery union angle, the contralateral approach may be difficult. In both cases, although this method may not be possible based on the patient’s vascular factors, we believe that it is important to understand the blood flow and maneuvers potentially causing distal embolization, and accordingly, develop procedures to avoid them.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients in whom mispuncture of the VA with a catheter became clear in the acute phase, leading to treatment, is small. 4 , 5) Al Rayes et al reported that stent-grafting for mispuncture of the right VA with a central venous catheter led to a favorable outcome, but there was no description of the postoperative course. 5) Tasopoulou et al presented a patient with a large subcutaneous hematoma related to mispuncture of the right VA on dialytic catheter insertion and reported that treatment with a covered stent resulted in angiographic cure.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The number of case reports in which acute-phase mispuncture required treatment is limited and there are no treatment guidelines. 4,5) We report a patient in whom an 8-Fr. sheath was misinserted into the right VA through the right IJV immediately before open heart surgery and endovascular therapy was performed immediately after mispuncture, leading to a favorable outcome.…”
Section: Introductionmentioning
confidence: 98%